2018
DOI: 10.1101/310748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide DNA methylation patterns in Autism Spectrum Disorder and mitochondrial function

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterised by phenotypic heterogeneity and overlapping co-morbidities. The genetic architecture of ASD is complex, with 100’s of risk genes cumulatively contributing to the aetiology of ASD. Epigenetic mechanisms, particularly DNA methylation, have been associated with ASD. The vast majority of ASD molecular research has focused on Northern European populations, with a paucity of data from Africa. This study examines genome-wide DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Mitochondrial genes have been reported to be differentially expressed in the cerebral cortex of ASD patients and strongly correlated with genes associated with synaptic transmission (Schwede et al, 2018), and in SCZ, disruptions in mitochondria have been found in different brain regions, cell types, and subcellular locations (Konradi and Ö ngü r, 2017). Recently, a human whole-genome methylation study revealed that two crucial biological processes, mitochondrial metabolism and protein ubiquitination, are associated with ASD brains (Stathopoulos et al, 2018). In agreement, a genome-wide association study (GWAS) showed significant enrichment for ASD-and SCZ-associated common variants in genes that regulate synapse and mitochondrial homeostasis (Gandal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial genes have been reported to be differentially expressed in the cerebral cortex of ASD patients and strongly correlated with genes associated with synaptic transmission (Schwede et al, 2018), and in SCZ, disruptions in mitochondria have been found in different brain regions, cell types, and subcellular locations (Konradi and Ö ngü r, 2017). Recently, a human whole-genome methylation study revealed that two crucial biological processes, mitochondrial metabolism and protein ubiquitination, are associated with ASD brains (Stathopoulos et al, 2018). In agreement, a genome-wide association study (GWAS) showed significant enrichment for ASD-and SCZ-associated common variants in genes that regulate synapse and mitochondrial homeostasis (Gandal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in DNAm can additionally be found in genes associated with oxidative phosphorylation (OXPHOS) in disease or with age. Such is the case in human patients with autism spectrum disorder (ASD) presenting differences in methylation of the genes encoding for complex I, such as NDUFA4 , NDUFB2 , NDUFB4 and NDUFB6 , complex III, like UQCRC2 , and complex IV, for instance COX7B [ 38 ]. Likewise, complex IV methylation alterations are also seen in non-diseased elderly human muscle tissue [ 39 ] and in laboratory high fat diet-induced insulin resistance rats [ 40 ], in the genes COX7A1 and Cox5a , respectively.…”
Section: Effects Of Nuclear Dna Methylation On Mitochondriamentioning
confidence: 99%
“…Recent studies have started to focus on addressing concerns of measuring mtDNA methylation raised in a number of investigations [ 38 41 ]. New methodologies have been presented which are specifically adapted to mitochondrial genomes to improve bisulfite conversion of mtDNA [ 47 ], and adapted to the analysis and methylation calling for this particular genome [ 15 ], yet do still acknowledge the limitations of some of these adaptations.…”
Section: Is Mitochondrial Dna Methylated?mentioning
confidence: 99%